If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -24 + -1x Solving y = -24 + -1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -24 + -1x
| 8-2(x-6)=-7x | | 6=2x+-2 | | x=2ln(6-y)+3 | | 3x+2=-20+30 | | -3(1-5r)=9+3r | | .04x+.07(1000-x)=660 | | 4b+20=60 | | F(x)=2ln(6-x)+3 | | -2m-5(1-5m)=110 | | 5+(x-9)+x=59 | | F(x)=xsq+x | | 2(x+12)+7(x-5)=4x-56 | | (8x-y-7)(6x)= | | x^3=41 | | 5y+36=10y+6 | | 0=x^3-3x-6 | | 4(2r+5)=6(r-2) | | 9-11x-7-10x=5 | | 6.1-r=3.4 | | 24d+40de= | | 4(z-3)+z=-2 | | -3(y-4)=18 | | -(9x-9)+9x= | | -3(7+5n)=-96 | | -1/3(2b-6) | | 3+4x+3=-2 | | X(7x-3)=(7x+8)(x-1) | | 7(2x-3)=3+2(x+5)+7 | | 11(-9-2x)=-(12x+11) | | i+30=28 | | 4(-5+x)=48 | | 3x+8=(6-x) |